REINFORCEMENT DALAM PEMBELAJARAN MEMBACA NYARING BAHASA INGGRIS (Penelitian Deskriptif Kualtatif di Kelas V Sekolah Dasar Negeri Citapen Kota Tasikmalaya) - AZIZAH, fahmi (2014)
The research was conducted as student's motivation in reading aloud is low. This is due to the they have difficulties in asosociating reding text with pronunciating it, understanding the reading text, and the bored them of teaching and learning process. Further more, the teacher should provide reinforcement. Reinforcement is all of teacher's respone to modify student's attitude with giving consequence. The teacher try to build student's learning motivation with reward or gift, punishment, and provide enjoy meaningfull learning. The purpose of the study is to describe the kinds and schedules of reinforcement that's used by the teacher in learning english reading aloud in the fifth grade of SD Negeri Citapen. The location of the research is in SD Negeri Citapen, and the subject of the research is the english teacher. The methode of teh research is qualitative descriptive methode, researcher describe the analysis result to the object of the research that is observed in natural condition when learning english teaching aloud. The data were collected trough observation and semistucture interview. The analysis was carried out based on the theory of B.F. Skinner and Cliff Turney. The analysis result of the data based on the theory of Skinner shows the english teacher in SD Negeri Citapen usually uses positive reinforment better than negative reinforcement. Positive reinforcement is reward and the negative reinforcement is punishment. The analysis result of the data based on theory of Cliff Turney shows that the reinforcement quantity used by the teacher is 531 times. The teacher did 180's verbal reinforcement with 33,90%. Gesture reinforcement is 147's with 27,68%, proximity reinforcement is 88's with 16,57%, token reinforcement is 86's with 16,20%, contact reinforcement is 23's with 4,33%, and activity reinforcement is 7's with 1,32%. Further more, the schedule of reinforcement that is used by the teacher is continous reinforcement schedule, which is each student's positively or negatively always given reinforcement by the theacher. Keyword: Learning english reading aloud, kinds of reinforcement, and schedule reinforcement.